(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Presentone case of complex bipolar dislocation andwarning the disadvantages of this arthroplasty. Method: Descriptive retrospective one - case presentation Case presented: Two-componenthead dislocation of bipolar ; revision, keep the stem and new bipolar head replaced. Result: One case of complex bipolar dislocation was presented, showing the unsatisfied resultsof this prosthesis and warn the surgeon ahead bipolar indication. Conclusion: In expectionfor replacement of total hip arthroplasty. But clinical reality shows that bipolar presumes replace the Moore prosthesis.